2016
DOI: 10.1016/j.fertnstert.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Age, independent from ovarian reserve status, is the main prognostic factor in natural cycle in vitro fertilization

Abstract: NC-IVF is a feasible and "patient-friendly" option to be offered to young patients, independent of their ovarian reserve status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
5
27
0
1
Order By: Relevance
“…In our study, 187 out of the 270 non-ART pregnancies ended up with live birth, suggesting the previously reported positive association of the EFI with the rate of live birth was mainly driven by its association with non-ART pregnancy. Although, age is frequently used to predict the chance of live birth or pregnancy [41,42], while lower ovarian reserve [43,44] and severity of the lesion [12,45] are the factors that might influence fertility outcomes, none of these studies were confined to the pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 187 out of the 270 non-ART pregnancies ended up with live birth, suggesting the previously reported positive association of the EFI with the rate of live birth was mainly driven by its association with non-ART pregnancy. Although, age is frequently used to predict the chance of live birth or pregnancy [41,42], while lower ovarian reserve [43,44] and severity of the lesion [12,45] are the factors that might influence fertility outcomes, none of these studies were confined to the pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pregnancy was defined as detection of embryonic heartbeat. The rates of implantation, clinical pregnancy, multiple pregnancy, and miscarriage were calculated [8].…”
Section: Controlled Ovarian Stimulation (Cos) and Ivf Proceduresmentioning
confidence: 99%
“…Although the Bologna criteria is useful for predicting ovarian response and counseling purpose, it grouped together women with various pathologies and characteristics [6]. Some have reported that, compared with elder patients, young poor ovarian responders demonstrated higher embryo quality and pregnancy rate but lower miscarriage rate [7][8][9]. Therefore, age has been proposed as an independent predictor for POR [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Поýтому до сих пор не теряет актуальности поиск возможных причин неýффективности программ ЭКО. Одним из приоритетных направлений современной репродуктологии является поиск морфологических, иммуно-гистохимических, молекулярных, генетических и клинических маркеров результативности программ ЭКО [3].…”
unclassified